2007
DOI: 10.1089/lap.2006.0114
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application and Diagnostic Yield of Wireless Capsule Endoscopy in Children

Abstract: WCE is a novel, noninvasive, and useful tool for the investigation of the small intestine in children. It is superior and more sensitive than other conventional endoscopic and radiologic investigations in the assessment of the small bowel. It can help in guiding surgical decisions and should be routinely integrated as a part of the diagnostic work-up of small bowel pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 25 publications
1
45
0
1
Order By: Relevance
“…Previous studies have proved the safety and efficacy of CE in the diagnosis of small bowel disease in pediatric patients [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In our study of 12 pediatric patients with suspected small bowel disease, CE revealed novel lesions in a patient with known CD that were undetectable by conventional exploration.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous studies have proved the safety and efficacy of CE in the diagnosis of small bowel disease in pediatric patients [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. In our study of 12 pediatric patients with suspected small bowel disease, CE revealed novel lesions in a patient with known CD that were undetectable by conventional exploration.…”
Section: Discussionmentioning
confidence: 57%
“…Studies of adult patients have revealed that CE is superior to the small bowel series for evaluating the small intestine [1][2][3]. A number of recent studies on pediatric patients have demonstrated that CE is also a useful in children with abdominal complaints, although the application of CE in this patient population has received relatively less attention compared to the adult patient population [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The indications for CE in both children and adults include obscure gastrointestinal bleeding (OGIB), Crohn's disease (CD), and lymphangiectasia; in adults, suspected tumors of the small bowel also suggest the need for CE [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Reports on a total of 466 pediatric patients including 105 with known and 138 with suspected CD, demonstrate the usefulness of capsule endoscopy in evaluation and management of these patients [11][12][13][14][15][16][17][18][19][20]. At the same time, however, gastric and intestinal capsule retention was seen in 13 (2.8%) and 18 (3.8%) of the total patients studied, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In an early paediatric study [357], suspected Crohn's disease was the most common indication. However, 5 of 37 children underwent SBCE for protein loss or malabsorption.…”
Section: Malabsorption Syndromesmentioning
confidence: 99%